2020
DOI: 10.1111/afe.12385
|View full text |Cite
|
Sign up to set email alerts
|

A study of landing behaviour by the walnut twig beetle,Pityophthorus juglandis, among host and nonhost hardwood trees in a northern California riparian forest

Abstract: The host selection behaviour of the walnut twig beetle, Pityophthorus juglandis, was assessed by monitoring the landing rates of the beetles with sticky sheet traps on the host and nonhost hardwood branches. 2 Sticky sheet traps were deployed for 8 weeks from 6 June to 2 August. 2017 in the Putah Creek Riparian Reserve, Davis, CA. Branches from host northern California black walnut, Juglans hindsii, were paired with branches from six nonhost hardwood species. 3 The landing rate of P. juglandis (412 beetles tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 45 publications
(85 reference statements)
0
7
2
Order By: Relevance
“…This indicates that Neuropterans may be present in high numbers throughout the Putah Creek Riparian Reserve. We also trapped a considerable number (53 specimens, Table 4) of Nathrius brevipennis , an invasive cerambycid, a finding that is consistent with other recent trapping studies (Audley et al ., 2020; Lona et al ., 2020). Additionally, we trapped two individuals of notable, relatively rare Coleoptera species, specifically Phymatodes vulneratus (Cerambycidae) and Trypophloeus thatcheri (Scolytidae), three Anobiidae species; Ptilinus sp., Petalium californicum , and Priobium punctatum .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This indicates that Neuropterans may be present in high numbers throughout the Putah Creek Riparian Reserve. We also trapped a considerable number (53 specimens, Table 4) of Nathrius brevipennis , an invasive cerambycid, a finding that is consistent with other recent trapping studies (Audley et al ., 2020; Lona et al ., 2020). Additionally, we trapped two individuals of notable, relatively rare Coleoptera species, specifically Phymatodes vulneratus (Cerambycidae) and Trypophloeus thatcheri (Scolytidae), three Anobiidae species; Ptilinus sp., Petalium californicum , and Priobium punctatum .…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides important context for the future management of thousand cankers disease. It provides field‐based evidence that WTB responds to long‐distance cues to identify and locate host trees during dispersal (Audley et al ., 2020). Additionally, it provides a foundation for future investigation of potentially repellent nonhost plant volatiles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brattli et al (1998) found that some bark beetle species were able to detect and differentiate between traps baited with host and nonhost material in flight in host, nonhost, and mixed (containing hosts and nonhosts) stands. Similarly, Audley et al (2020b) showed that Pityophthorus juglandis Blackman (Coleoptera: Curculionidae) can discriminate between hosts and nonhosts while in flight.…”
Section: Introductionmentioning
confidence: 99%